2019
DOI: 10.1002/pc.25224
|View full text |Cite
|
Sign up to set email alerts
|

Laser surface treatment of CFRP composites for a better adhesive bonding owing to the mechanical interlocking mechanism

Abstract: Adhesion can be greatly improved by the correct surface preparation techniques. One of the most common and useful technique is specific surface structuring which leads to mechanical interlocking and greater adhesion. This work describes the effect of laser-induced line pattern surface structuring on the mechanical interlocking mechanism and so on the adhesive bonding of carbon fiber reinforced polymer (CFRP) composites. Surface patterns with different laser scribes were obtained by CO 2 laser treatment. The ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Thermoplastic-thermoset MMCs combine the damage tolerance characteristics, and welding capability of thermoplastics with the strength and stiffness of thermoset composites resulting in more reliable structures with an extended lifetime [ 4 , 5 , 6 ]. However, joining thermoplastics to thermosets remains a challenging step despite the development of various joining technologies for composite structures including (i) mechanical fastening [ 7 , 8 , 9 ], (ii) welding [ 10 , 11 , 12 , 13 ], (iii) adhesive bonding [ 14 , 15 , 16 ], (iv) co-curing (parts are cured at the same time) [ 17 , 18 ], and (v) hybrid joints (combination of two or more of previous methods) [ 19 , 20 , 21 ]. Nevertheless, all these joining methods have disadvantages in terms of being unreliable, labour-intensive, time-consuming and expensive [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thermoplastic-thermoset MMCs combine the damage tolerance characteristics, and welding capability of thermoplastics with the strength and stiffness of thermoset composites resulting in more reliable structures with an extended lifetime [ 4 , 5 , 6 ]. However, joining thermoplastics to thermosets remains a challenging step despite the development of various joining technologies for composite structures including (i) mechanical fastening [ 7 , 8 , 9 ], (ii) welding [ 10 , 11 , 12 , 13 ], (iii) adhesive bonding [ 14 , 15 , 16 ], (iv) co-curing (parts are cured at the same time) [ 17 , 18 ], and (v) hybrid joints (combination of two or more of previous methods) [ 19 , 20 , 21 ]. Nevertheless, all these joining methods have disadvantages in terms of being unreliable, labour-intensive, time-consuming and expensive [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] The schematic of laser surface treatment is shown in Figure 1. Çoban et al [ 6 ] obtained the surface patterns of different laser scribes through CO 2 laser treatment to study the influence of surface structure on the adhesive bonding strength of carbon fiber composites. The mechanical interlocking mechanism can be obtained by optimizing the laser scribing mode to improve the strength of CFRP joint.…”
Section: Adhesive Processmentioning
confidence: 99%
“…These surface treatment creates macro roughness on composite surface, causes poor adhesion, are labor‐intensive, and etch the surface heterogeneously. [ 18 ] Sezer [ 15 ] reported that chemical etching is an alternative route for the modification of composite surfaces in the microelectronic industry. These etchants interact with the polymer matrix physically, etch the surface homogenously, and create micromechanical interlocking between the adhesive and composite surface.…”
Section: Introductionmentioning
confidence: 99%